RELEVANCE OF CORPORATE SOCIAL RESPONSIBILITY WITH TRI HITA KARANA - Nengah Sukendri; I Nyoman Nugraha Ardana Putra (Finance and Investment Program, School of Business and Management - Petra Christian University, 2022)
Tri Hita Karana is a Balinese culture that has been famous to the world. This article hopes to provide a view and open the insight that the concept of Tri Hita Karana, which turned out to have carried the idea of ​​Corporate Social Responsibility, was only heard when entering the millennium era. The method used is a literature study method that uses secondary data in peeling and pulling the common thread of both existing concepts. There is a relevant relationship between the two images, where the idea of ​​Balinese culture, which is a concept that pays attention to the relationship with God Almighty, the relationship with fellow humans, and the surrounding environment, is strongly related to napa described in Corporate Social Responsibility.